The Effect of Cloud Accounting Adoption on Financial Reporting Efficiency with Digital Literacy as a Moderating Variable in MSMEs - Putri, Arie Pradina (Global Education Journal, 2025)
Transparency of public information is an important pillar in good governance. This study aims to examine how the implementation of cloud-based accounting affects the efficiency of financial reporting, as well as to assess the role of digital literacy in strengthening this relationship among Micro, Small, and Medium Enterprises (MSMEs) in Pontianak City. The research method uses a quantitative approach with a causal research design, data were collected through a survey given to 100 MSME owners who met the research criteria. The questionnaire was developed using a Likert scale, and responses were analyzed using Moderated Regression Analysis (MRA) with the help of SPSS version 26. The results showed that the adoption of cloud-based accounting has a positive and significant effect on the efficiency of financial reporting (significance value = 0.001; p < 0.05). In addition, digital literacy was confirmed to act as a moderating variable that strengthens the relationship between the use of cloud-based accounting and financial reporting efficiency, evidenced by an interaction coefficient of 0.122 and a significance level of 0.037. This indicates that MSMEs with higher digital skills are better able to optimize the benefits of cloud-based accounting systems, particularly in improving the speed and accuracy of financial reports. Overall, this study highlights that the success of digital transformation in the MSME sector is influenced not only by technological infrastructure but also by the digital competence of users. The results of this study are expected to contribute to the literature on accounting information systems and serve as a reference for local governments and supporting institutions in designing digital literacy improvement programs that encourage the sustainable adoption of cloud accounting.